A study of Funerary Culture in Mongol Oral Tradition: Rituals of Inhumation and Rock Burial - Ishdorj, Davaadorj (Studia Folclorica, 2025)
This paper explores core aspects of Mongol funerary culture, focusing specifically on burial rituals and forms. The analysis draws on ethnographic fieldwork, primary source materials, and examples from Mongol folklore. We examine these rituals through the lens of the five elements (earth, fire, water, wood, and rock/metal), which form a cohesive symbolic system within Mongol mythology and symbology. Using this framework, we categorize burial types according to their associated elements. This article provides an in-depth analysis of earth and rock (metal) burial traditions. Among these various forms, earth and fire burials have survived to the present day. According to oral accounts, earth burial spread alongside the rise of Buddhism and often coexisted with sky burial (the practice of open-air exposure burials) practices. By contrast, rock or metal-related burial customs reflect older belief systems rooted in shamanism. These older practices were gradually replaced due to socio-historical and religious transformations. Oral histories frequently describe associated rituals-such as land divinition and the use of specialized tools-underscoring their integral role within the broader funerary system. Алтай хайлах дэгийн онцлог Монгол аман уламжлалаас оршуулгын соёлыг шинжлэх нь (шороо болон хаданд оршоох ёсны тухай) Хураангуй: Монголчуудын оршуулгын соёл, зан үйлийн гол хэсэг болох оршуулах ёс, хэлбэрийг угсаатны зүйн хээрийн судалгааны тайлан, эх хэрэглэгдэхүүн, монгол аман зохиолын жишээ баримтад тулгуурлан, монгол домог, бэлгэдэл зүйн нэгэн цогцолбор хэсэг болох таван махбод, өнгийн санаатай холбон авч үзлээ. Эл санаанд түшиглэн оршуулах ёс, хэлбэрийг шороо, гал, ус, мод, хад (төмөр)-д оршоох хэмээн ангилж, эл өгүүлэлд шороо болон хад (төмөр)-наа оршоох ёсыг задлан шинжилж, тайлан тайлбарлалаа. Оршуулгын ёс, хэлбэрээс шороо, галд оршуулах ёс өнөөг хүртэл хадгалан үлдсэн бөгөөд шороонд оршуулах ёсыг Бурханы шашны дэлгэрэлттэй холбоотой түгсэн ил хөдөөлүүлэх ёстой зэрэгцэн оршиж байсныг аман мэдээнээс нотолж болно. Харин хад буюу төмөр махбодод оршуулах соёл нь шүтлэгийн уламжлалт хэлбэр, бөө мөргөлтэй холбогдож, нийгэм-түүх, шашин соёлын нөлөөгөөр оршуулгын бусад хэлбэрээр халагдан солигджээ. Үүний зэрэгцээ аман түүхнээ газар шинжих, гуйх зан үйлд ашиглах хэрэгслийг цөөнгүй дурдсан нь оршуулах соёл, зан үйлийн чухал хэсэг болохыг харуулж байна. Түлхүүр үг: оршуулгын соёл, зан үйл, таван махбод, таван өнгө, аман түүх